Stations, stations, stations : Les Cents jours d'art contemporain de Montréal : 1 août-2 novembre 1987. - Lapointe, Manon; Brouillette, Carole; Gosselin, Claude; Bellemare, Roger; Schaer, Roland; Newmann, Barnett; Campbell, James D; Tremblay, Suzanne; Centre international d'art contemporain de Montréal, Montréal (Montréal : Centre international d'art contemporain de Montréal, 1988)
Müller, Josef Felix ; Fischl, Eric ; Golub, Leon ; Baselitz, Georg ; Abramovic, Marina ; Ulay ; Heward, John ; Rainer, Arnulf ; Spero, Nancy ; Lemyre, Marcel ; Nauman, Bruce ; Bourgeois, Louise ;; Baldessari, John ; Goodwin, Betty ; Michals, Duane ; et al.
Centre International d'Art Contemporain de Montréal, Montréal, 1 août - 2 novembre 1987
kunstcatalogus
Keywords: Canada